The Long Noncoding RNA HEAL Regulates HIV-1 Replication through Epigenetic Regulation of the HIV-1 Promoter - Ti-Chun Chao (American Society for Microbiology, 2019)
ABSTRACT A major challenge in finding a cure for HIV-1/AIDS is the difficulty in identifying and eradicating persistent reservoirs of replication-competent provirus. Long noncoding RNAs (lncRNAs, >200 nucleotides) are increasingly recognized to play important roles in pathophysiology. Here, we report the first genome-wide expression analysis of lncRNAs in HIV-1-infected primary monocyte-derived macrophages (MDMs). We identified an lncRNA, which we named HIV-1-enhanced lncRNA (HEAL), that is upregulated by HIV-1 infection of MDMs, microglia, and T lymphocytes. Peripheral blood mononuclear cells of HIV-1-infected individuals show elevated levels of HEAL. Importantly, HEAL is a broad enhancer of multiple HIV-1 strains because depletion of HEAL inhibited X4, R5, and dual-tropic HIV replications and the inhibition was rescued by HEAL overexpression. HEAL forms a complex with the RNA-binding protein FUS, which facilitates HIV replication through at least two mechanisms: (i) HEAL-FUS complex binds the HIV promoter and enhances recruitment of the histone acetyltransferase p300, which positively regulates HIV transcription by increasing histone H3K27 acetylation and P-TEFb enrichment on the HIV promoter, and (ii) HEAL-FUS complex is enriched at the promoter of the cyclin-dependent kinase 2 gene, CDK2, to enhance CDK2 expression. Notably, HEAL knockdown and knockout mediated by RNA interference (RNAi) and CRISPR-Cas9, respectively, prevent HIV-1 recrudescence in T cells and microglia upon cessation of azidothymidine treatment in vitro. Our results suggest that silencing of HEAL or perturbation of the HEAL-FUS ribonucleoprotein complex could provide a new epigenetic silencing strategy to eradicate viral reservoirs and effect a cure for HIV-1/AIDS. IMPORTANCE Despite our increased understanding of the functions of lncRNAs, their potential to develop HIV/AIDS cure strategies remains unexplored. A genome-wide analysis of lncRNAs in HIV-1-infected primary monocyte-derived macrophages (MDMs) was performed, and 1,145 differentially expressed lncRNAs were identified. An lncRNA named HIV-1-enhanced lncRNA (HEAL) is upregulated by HIV-1 infection and promotes HIV replication in T cells and macrophages. HEAL forms a complex with the RNA-binding protein FUS to enhance transcriptional coactivator p300 recruitment to the HIV promoter. Furthermore, HEAL knockdown and knockout prevent HIV-1 recrudescence in T cells and microglia upon cessation of azidothymidine treatment, suggesting HEAL as a potential therapeutic target to cure HIV-1/AIDS.